(untitled) (International Journal of Engineering and Computer Science, 2017)
A pattern is an entity that could be named, e.g. fingerprint image, handwritten word, human face, speech signal, DNA sequence and many more. Pattern recognition has its roots in artificial intelligence(AI). Pattern recognition is the study of how machines can learn to distinguish patterns and make some decisions about the categories of the patterns. Medical and healthcare sector are a big industry nowadays. Image based medical diagnosis is one of the important service areas in this sector. Various artificial intelligence techniques such as artificial neural network and fuzzy logic are used for classification problems in the area of medical diagnosis. Most of these computer-based systems are designed by using artificial neural network techniques. Electronic health records (EHR) provide detailed, time-stamped, and highly multivariate data for a large patient population, enabling the use of AI techniques to connect care practices and outcomes.